Atmospheric Microplastic Particulate Matter in an Urban Roadside: Case of Bandar Lampung City, Indonesia - Sari, Novi Kartika; Mawaddah, Nurul; Shiddiq, Muhammad Daffa; Alam, Firdha Cahya; Fajar, Mutiara (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Atmospheric microplastics (AMPs) have become a growing concern in recent years, although research remains limited. This study investigated AMPs in Bandar Lampung City, Indonesia, by roadside particulate sampling using a High-Volume Air Sampler (HVAS) over eight hours in industrial zones, residential areas, busy roads, and city centers. AMPs were identified through visual analysis for their abundance and physical characteristics. Certain samples were further examined with Raman spectroscopy. Total Suspended Particulate (TSP) levels ranged from 16.96 to 427.8 μg/m³, with the highest concentrations in industrial areas. Microplastic concentrations ranged from 0.0021 to 0.0199 particles/m³, with fibrous microplastics most common. Blue and grey (faded black) microplastics were the most prevalent, with particles between 500-1000 µm making up 42% of the total. Raman analysis detected Polyethylene terephthalate (PET). In S4 (city center), the highest vehicle count was 3,388±270 vehicles/day, while S2 (residential area) recorded the lowest at 1,166±99 vehicles/day. No significant relationship was found between TSP levels, microplastic concentrations, or vehicle numbers. However, Northern area may be potential sources of AMPs along traffic flow.